Project-Based Learnıng Strategıes To Optımıze The Intellectual Intellıgence Of Elementary School Students - Azizah, Anita Rosti; Suwandayani, Beti Istanti; Arifin, Bustanol (Elementary Teacher Education Program, Majalengka University, 2024)
In the 21st century, civilization and technology are advancing, so students need more than just theoretical abilities; they need to develop creative and innovative abilities that can balance the abilities required for the future. Project-based learning emerged as one of the effective alternatives, which provides opportunities for students to be directly involved in real experiential learning and allows them to apply what they have learned to various conditions in everyday life. Therefore, this study aims to illustrate how project-based learning can optimize the intellectual intelligence of elementary school students, especially class V-B cultural arts and crafts material written batik. This method uses a qualitative descriptive approach with informants, namely class teachers and students V-B SDN Dadaprejo 01. Data was collected through observation, interviews, and documentation. The results show that project-based learning strategies contribute to better intellectual intelligence. Students' ability to carry out activities, actively discuss, and complete tasks shows their intellectual intelligence. Their great curiosity and critical questions during learning reflect their interest in learning and developed thinking. This positively impacts their academic achievement and equips them to face future educational challenges.